Dinamika Posisi Subjek dan Objek Perempuan dalam Ruang Publik Digital pada Film Budi Pekerti: Analisis Wacana Kritis Sara Mills - Hasna Arridha Hayati; Sudiati Sudiati; Maman Suryaman (Jurnal Bahasa dan Sastra, 2026)
The film Budi Pekerti depicts the vulnerability of women in the digital space due to patriarchal culture through the character of Bu Prani, who becomes a victim of cyberbullying. This study aims to describe the construction of women’s positions as subjects and objects in the film Budi Pekerti by Wregas Bhanuteja through the lens of Sara Mills’ Critical Discourse Analysis. The study employs a qualitative descriptive approach, utilizing data consisting of dialogue, speech acts, narrative, and scenes from the film Budi Pekerti. Data were collected through observation using the non-participant observation technique, which involves observing, noting, recording, and transcribing. Data analysis utilized the interactive model by Miles, Huberman, and Saldana, which includes data collection, data condensation, data presentation, and drawing conclusions. The results of the study indicate that women’s positions in the film Budi Pekerti are constructed through two primary roles: subject and object. Twenty-nine instances were identified that reflect the subject role, in which women are portrayed as conveyors of perspectives, decision-makers, and evaluators. Meanwhile, eight instances were identified that reflect the object role, in which women are positioned as targets of public judgment, representations in digital media, and social stereotypes. The dominance of the subject position indicates that female characters are constructed as active agents who fight for space to express their perspectives, construct meaning, and defend their views amidst various social pressures. However, female characters are also positioned as objects that become targets of judgment, labeling, and meaning-making by others. These findings indicate that the position of women in the film Budi Pekerti is dynamic. Furthermore, the digital space plays a role in influencing the shifting position of women as both subjects and objects in the construction of discourse.